2009
DOI: 10.1097/mao.0b013e3181b05023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tonic and Burst Transcranial Magnetic Stimulation Characteristics on Acute Inhibition of Subjective Tinnitus

Abstract: Several parameters determine the amount of tinnitus reduction after TMS. An increased stimulation intensity relative to the patient's motor threshold only accounts for 10% of this effect. Our data also suggest different pathophysiologic mechanisms for unilateral and bilateral tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…After examining the effectiveness of tonic and burst TMS on 46 patients with narrow band or white noise tinnitus, De Ridder et al [2007] found the following: (1) response rate was 30.4%; (2) burst TMS resulted in better tinnitus suppression than tonic TMS; (3) alpha and beta burst, as well as theta burst, can be used to control narrow band noise or white noise tinnitus. Later, the same group suggested that burst TMS can be used to control noise-like tinnitus, while tonic TMS resulted in greater tinnitus reduction on pure tone tinnitus [Meeus et al, 2009]. Our outcomes also indicate that theta-burst rTMS can have a significant effect on pure-tone tinnitus (42% of patients experienced 1 33% reduction in tinnitus).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…After examining the effectiveness of tonic and burst TMS on 46 patients with narrow band or white noise tinnitus, De Ridder et al [2007] found the following: (1) response rate was 30.4%; (2) burst TMS resulted in better tinnitus suppression than tonic TMS; (3) alpha and beta burst, as well as theta burst, can be used to control narrow band noise or white noise tinnitus. Later, the same group suggested that burst TMS can be used to control noise-like tinnitus, while tonic TMS resulted in greater tinnitus reduction on pure tone tinnitus [Meeus et al, 2009]. Our outcomes also indicate that theta-burst rTMS can have a significant effect on pure-tone tinnitus (42% of patients experienced 1 33% reduction in tinnitus).…”
Section: Discussionsupporting
confidence: 63%
“…dorsolateral prefrontal cortex). One popular paradigm for tinnitus is low-frequency tonic stimulation (mostly at 1 Hz, with an intensity of 110-120% RMT), although time-saving burst stimulation has become increasingly popular in recent years [Richter et al, 2006;Arfeller et al, 2009;Meeus et al, 2009]. The 1-Hz protocol takes 25 min, whereas the TBS (consisting of 900 pulses per session), takes less than 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Vanneste et al (66) concluded that rMT cannot be assumed to be a guide to auditory cortex excitability because ''excitatory measurements of one specific cortex cannot be generalized to the excitability of the whole cortex.'' Also, in a study that used different TMS stimulus intensities with tinnitus patients, Meeus et al (67) stated, ''Increasing the TMS stimulation intensity [in relation to] the patient's motor threshold only plays a minor role in achieving higher tinnitus reduction.'' In fact, Meeus et al (67) reported that increasing TMS intensity above 50% of their Magstim system's maximum output accounted for only 10% improvement in tinnitus suppression.…”
Section: Intensitymentioning
confidence: 98%
“…Also, in a study that used different TMS stimulus intensities with tinnitus patients, Meeus et al (67) stated, ''Increasing the TMS stimulation intensity [in relation to] the patient's motor threshold only plays a minor role in achieving higher tinnitus reduction.'' In fact, Meeus et al (67) reported that increasing TMS intensity above 50% of their Magstim system's maximum output accounted for only 10% improvement in tinnitus suppression. Until there is a greater degree of standardization, it is difficult to determine the TMS intensity that is most effective for reducing the perception or severity of tinnitus.…”
Section: Intensitymentioning
confidence: 98%